1971
DOI: 10.1115/1.3449800
|View full text |Cite
|
Sign up to set email alerts
|

Combining Forced and Free Convective Equations to Represent Combined Heat-Transfer Coefficients for a Horizontal Cylinder

Abstract: An analytical correlation of superposed free and forced convection for air for a horizontal cylinder in which the forced convection and free convection forces act in the same direction is considered. A simplified method by which the ordinary formulas for forced convection and for free convection can be used together to give the Nusselt number is presented. The method proposed herein can easily be modified to work for other combinations of free and forced flow systems. The method, therefore, may have wide appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The result for assisting flow is equivalent to Equation ( 2 ) with n = 4. Jackson and Yen (1971) recorrelated the data of Oosthuizen and Maden (1970) for assisting flow of air over heated horizontal cylinders using the equivalent of Equation (2) with p = ?h, q = 1/4, n = 4, and E / F = 1. They rationalized the exponent of 4 on the basis of the additivity of the work of free and forced convection.…”
Section: Previous Workmentioning
confidence: 99%
“…The result for assisting flow is equivalent to Equation ( 2 ) with n = 4. Jackson and Yen (1971) recorrelated the data of Oosthuizen and Maden (1970) for assisting flow of air over heated horizontal cylinders using the equivalent of Equation (2) with p = ?h, q = 1/4, n = 4, and E / F = 1. They rationalized the exponent of 4 on the basis of the additivity of the work of free and forced convection.…”
Section: Previous Workmentioning
confidence: 99%
“…This hybrid finite element–finite volume code used in the present work was thoroughly validated earlier by solving a number of benchmark problems, such as the flow in lid-driven square cavity, steady flow past a circular cylinder, unsteady flow past a circular cylinder, flow in a backward facing step and natural convection flow and heat transfer in a temperature-driven cavity. 26 For the present problem also, an attempt has been made to validate the code by comparing the computed Nu with the value obtained from equation (4) reported in Jackson and Yen, 27 Kieft et al., 28 and Badr. 29 The comparison given in Table 3 shows the validity of the present numerical method.…”
Section: Resultsmentioning
confidence: 83%
“…It is found that the average Nusselt number decreases as ( λ ) increases. This is because the buoyancy forces aid the flow around most of cylinder surfaces, and this effect decreases as ( λ ) increases (see Figure (5)). A comparison with previous theoretical and experimental results as shown in figures (6 and 7).…”
Section: Resultsmentioning
confidence: 99%
“…Combined free and forced convection from the horizontal cylinders, at different angles of air flow direction, was experimentally invest igated by Oosthuizen and Madan [2]. Other experimental studies are found in References [3][4][5]. On the other hand, the influence of free stream direction on Mixed convection heat transfer from a circular cylinder was numerically investigated by Badr [6].The cylinder, which has an isothermal surface, is placed with its axis horizontal and normal to the oncoming flow.…”
Section: Introductionmentioning
confidence: 99%